2017
DOI: 10.1039/c6dt04796c
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hybrid ABX3perovskite compounds for solar cell application: first-principles calculations of effective ionic radii and determination of tolerance factors

Abstract: The development of hybrid organic-inorganic perovskite solar cells is one of the most rapidly growing fields in the photovoltaic community and is on its way to challenge polycrystalline silicon and thin film technologies. High power conversion efficiencies can be achieved by simple processing with low cost. However, due to the limited long-term stability and environmental toxicity of lead in the prototypic CHNHPbI, there is a need to find alternative ABX constitutional combinations in order to promote commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(154 citation statements)
references
References 79 publications
6
146
0
Order By: Relevance
“…Although most of the cations are either too large or small to form a 3D perovskite phase on their own, they can be partially substituted into MAPbI 3 to create binary mixed-cation systems. 19,25,26 As phase separation can occur above certain substitution ratios, A-site doping was limited experimentally to 5% corresponding to MA 0.95 A 0.05 PbI 3 . Although it has been reported that Rb does not act as an A-site cation in FA-based perovskites, it can be incorporated alongside other smaller additives.…”
Section: Partial Substitution Of a Range Of A-site Cationsmentioning
confidence: 99%
“…Although most of the cations are either too large or small to form a 3D perovskite phase on their own, they can be partially substituted into MAPbI 3 to create binary mixed-cation systems. 19,25,26 As phase separation can occur above certain substitution ratios, A-site doping was limited experimentally to 5% corresponding to MA 0.95 A 0.05 PbI 3 . Although it has been reported that Rb does not act as an A-site cation in FA-based perovskites, it can be incorporated alongside other smaller additives.…”
Section: Partial Substitution Of a Range Of A-site Cationsmentioning
confidence: 99%
“…In fact, this idea has recently been emerging with some datasets of hybrid organic/inorganic perovskites, prepared at some level of computations 27,28 . Our dataset, which contains 1,346 HOIPs, is prepared uniformly at the level of density functional theory (DFT) 29,30 from the initial structures predicted by the minima-hoping method 31,32 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Imidazole (IZ) has a reasonable ionic radius of 258 pm with an aromatic structure, allowing good solid solution with MAPbI 3 . Moreover, the diammonium molecule can provide additional hydrogen bonding for a stable material, and due to the delocalized π orbital of IZ with hydrogen bonding in a I–Pb cage, it may allow low reactivity with its surroundings leading to additional electrical conductivity. Thereby, the devices with IZ‐alloyed MAPbI 3 have achieved reverse PCEs up to 20.2% with outstanding stability from light‐, air‐, and heat‐induced environments.…”
Section: Introductionmentioning
confidence: 99%